Piezosurgery-Assisted Surgical Treatment in Impacted Canine Transmigration - Matheus Francisco Barros Rodrigues; Layla Louise de Amorim Rocha; Rodrigo da Franca Acioly; Cristofe Coelho Lopes da Rocha; Daniel do Carmo Carvalho (Case Reports in Dentistry)
Delayed eruption of a canine tooth may represent a possible impaction. If this is the case, a slight elevation in the palatal or vestibular mucosa is often observed. Cases of transmigration, where the unerupted tooth crosses the midline, are less frequent. This article reports on the piezosurgery-assisted surgical treatment of a transmigrated canine in the mentonian region. Treatment for this condition varies depending on the clinical characteristics, symptoms, and location of the dental element. The surgical treatment established for this case was satisfactory, and full recovery of the patient was achieved without complications such as an intense postoperative inflammatory response.